2015
DOI: 10.1038/ncomms7338
|View full text |Cite
|
Sign up to set email alerts
|

Two linked pairs of Arabidopsis TNL resistance genes independently confer recognition of bacterial effector AvrRps4

Abstract: Plant immunity requires recognition of pathogen effectors by intracellular NB-LRR immune receptors encoded by Resistance (R) genes. Most R proteins recognize a specific effector, but some function in pairs that recognize multiple effectors. Arabidopsis thaliana TIR-NB-LRR proteins RRS1-R and RPS4 together recognize two bacterial effectors, AvrRps4 from Pseudomonas syringae and PopP2 from Ralstonia solanacearum. However, AvrRps4, but not PopP2, is recognized in rrs1/rps4 mutants. We reveal an R gene pair that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
157
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 65 publications
5
157
0
1
Order By: Relevance
“…S6B). RRS1B and RPS4B (Saucet et al, 2015) were present in all accessions, flanked by 12 differentially methylated TEs (Helitron and MuDR) (Fig. 7F and S6B).…”
Section: Resultsmentioning
confidence: 98%
“…S6B). RRS1B and RPS4B (Saucet et al, 2015) were present in all accessions, flanked by 12 differentially methylated TEs (Helitron and MuDR) (Fig. 7F and S6B).…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, Saucet et al. 20 suggested that A. thaliana accession RLD-0 lacks function of both RPS4/RRS1 and RPS4B/RRS1B. In this study, we showed that RPS4-Ws transferred RLD-0 plants, containing nonfunctional RPS4B/RRS1B, were resistant to the pathogens and RPS4-Ws Y950H complemented rps4-21 plants (Ws-2 background, containing functional RPS4B/RRS1B) were compatible to the pathogen.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, Saucet et al. 20 reported that RPS4B ( At5g45060 )/ RRS1B ( At5g45050 ) is paralogous and functionally similar to RPS4 / RRS1 . RPS4B and RRS1B recognize AvrRps4 but not PopP2.…”
Section: Resultsmentioning
confidence: 99%
“…RRS1B/RPS4 or RRS1‐R/RPS4B) leads to nonfunctional complexes, TIR domain swaps between these two protein pairs retain effector recognition function. This suggests that the TIR domains have similar roles for effector‐triggered activation in both paired NLRs (Saucet et al ., ). RRS1B and RRS1‐R TIR domains share ~70% identity at the amino acid level and the S25H26 motif (S22H23), C15 (C12) and P68 (P63) residues are located in highly conserved regions of RRS1‐R and RRS1B, respectively (Fig.…”
Section: Resultsmentioning
confidence: 97%